STRATEGI PENGEMBANGAN KEPEMIMPINAN PROFETIK-TRANSFORMASIONAL DI LEMBAGA PENDIDIKAN ISLAM: NARRATIVE REVIEW MENUJU MODEL KEPEMIMPINAN ISLAM ADAPTIF - Hasanah, Uswatun; Efendi, M, Nur; Aziz, Abdul (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2026)
Islamic Education Institutions in Indonesia (LPI) often face double pressures: implementing prophetic values amidst modernization and digitalization. This article uses narrative review with thematic synthesis approach, screening from 212 artcles into 14 scientific articles indexed by Sinta1-3 and Scopus during 2019-2026 period. The selected articles discuss leadership development strategies in Islamic boarding schools, madrasas, and private Islamic schools in Indonesia. Prisma protocol was used in seleecting and reviewing the articles. There are 5 themes taken from the thematic analysis: 1) prophetic and transformational synergy as the foundation; 2) social capital as a leadership infrastructure; 3) the paradox of integrating technology and Islamic tradition; 4) hidden structural bariers in leadership implementation; and 5) directions towards an integratif leadership model. The five themes propose an Adaptive Islamic Leadership Model (Manajemen Kepemipinan Islam Adaptif / MKIA) with its three pilars: the SATF+Shura prophetic values, managerial-transfromational competencies, and social capital-based contextual responsivemness. This contribution shares a rarely discussed topic of the integration of the Islamic educational management theory using separate theoretical lenses and identifying theoretical propositions as well as the structural bariers.